2009
DOI: 10.1186/1479-5876-7-52
|View full text |Cite
|
Sign up to set email alerts
|

Is there a relationship between factor V Leiden and type 2 diabetes?

Abstract: Background: Diabetes is well known risk factor for thrombotic events. The association between diabetes and venous thromboembolism is still matter of debate. However, during diabetes an acquired thrombophilia is present and is due to the non-enzymatic glycosilation of clotting inhibitors as antithrombin thus leading to hypercoagulable state. A possibile relationship between the presence of FVL gene variant in type 1 or type 2 diabetes has been hypothysed by several reports in the Literature with non-univocal fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 19 publications
0
12
0
1
Order By: Relevance
“…It has been reported that genetic factors could explain about 10 % of the variation in functional ability among older Danish male twins and 30 % among female twins (Christensen et al 2003). The ApoE gene is associated with Alzheimer Disease and heart diseases (Eichner et al 2002); other genetic abnormalities also are shown to be responsible for early-onset hypertension (Yang et al 2009) and diabetes (Lodigiani et al 2009). Furthermore, several localized samples have shown that interactions of ApoE-e4 with gender and baseline functional status predicted functional decline; the ApoE-e4 allele was not independently associated with declines in functional status or cognition (Blazer et al 2001).…”
Section: Genetic or Biological Factorsmentioning
confidence: 97%
“…It has been reported that genetic factors could explain about 10 % of the variation in functional ability among older Danish male twins and 30 % among female twins (Christensen et al 2003). The ApoE gene is associated with Alzheimer Disease and heart diseases (Eichner et al 2002); other genetic abnormalities also are shown to be responsible for early-onset hypertension (Yang et al 2009) and diabetes (Lodigiani et al 2009). Furthermore, several localized samples have shown that interactions of ApoE-e4 with gender and baseline functional status predicted functional decline; the ApoE-e4 allele was not independently associated with declines in functional status or cognition (Blazer et al 2001).…”
Section: Genetic or Biological Factorsmentioning
confidence: 97%
“…Diabetes may increase the levels of some coagulation factors and impair the fibrinolytic system, leading to a hypercoagulability state . Furthermore, compared with controls, an association has been reported between latent diabetes in carriers of factor V Leiden with previous VTE . Other factors that can contribute to prothrombotic status in diabetes include chronic inflammation, primary changes in haemostasis, enhanced oxidative stress and decreased expression of protective endothelial factors .…”
Section: Introductionmentioning
confidence: 99%
“…Apart from the congenital defect mentioned above, acquired defects such as aberration in the vascular wall and stagnation of blood flow also cause thrombosis. ‘Economy class syndrome’ (deep venous thrombosis) is a representative condition of acquired thrombosis [3,4]. …”
Section: Introductionmentioning
confidence: 99%